Wild edible plants sustaining food security among indigenous communities in Kashmir Himalayas, India - Shaista Khan
Gujjar and Bakarwal communities of Kashmir Himalayas living in remote and mountainous regions possess limited resources to sustain their life. The local wild edibles are still utilized traditionally by these tribal communities, but this traditional knowledge is yet to be documented. Therefore, the present research was conducted to explore and prospect the wild edible plants traditionally consumed by the tribal communities in India. Field appraisals included preparation of semi-structured interview schedules, interview of primary respondents, participatory observation and open listing. A total number of 111 respondents were selected by employing the multistage random sampling approach and information regarding Wild Edible Plants (WEPs) was collected. The Relative Frequency of Citation (RFC) was evaluated to recognize the most culturally important WEPs among indigenous communities. A total of 55 plant species of WEPs extracted by the indigenous people corresponding to 45 genera and 31 families were documented. Among all the species, Malva neglecta demonstrated the highest RFC value (0.87) whereas Taxus contorta with the least RFC value of 0.03. The WEPs used by the Gujjar and Bakarwal tribes are diverse and prolific in the Himalayan region. The present study could be a keystone to be reformulated in other regions of India as well as to be wide spreading through nutrigenomics and pharmacological explorations in order to sustain traditional native knowledge.